Application of neuromuscular electrical stimulation of the lower limb skeletal muscles in the rehabilitation of patients with chronic heart failure and chronic obstructive pulmonary disease - Kucio, Ewa Barbara; Niesporek, Justyna; Kucio, Cezary (Family Medicine & Primary Care Review, 2017)
Increasing physical activity is a widely-known method of rehabilitation of patients with chronic heart failure (CHF) and chronic obstructive pulmonary disease (COPD). However, what kind of procedure is to be applied if a patient suffers from advanced heart or respiratory failure, cannot undertake physical exercise due to locomotor system disorders or is currently undergoing respiratorotherapy? Recent research shows that neuromuscular electrical stimulation of the lower limb skeletal muscles (NMES) may comprise an alternative to physical training in patients with CHF and COPD. The aim of this study is to summarize the current state of knowledge on the use of NMES in cardiac rehabilitation of patients with CHF and pulmonary rehabilitation of patients with COPD. As demonstrated in recent research on the topic, NMES – due to forcing the muscles to activate – increases exercise tolerance, muscle mass and endurance in patients with CHF and COPD. The beneficial effect of NMES on blood circulation in the muscles, aerobic enzymes activity, functioning of the vascular endothelium, reduction of pro-inflammatory cytokines concentration and increased quality of life has also been presented. It is to be accentuated that NMES treatment, due to lesser physical exertion and, in turn, a decreased feeling of dyspnea are more comfortable for the patient than traditional physical training. Moreover, NMES treatment, after foregoing training, can be applied at home. Potential side effects include transient muscle pain and minor skin damage due to improper positioning of the electrodes. To summarize, NMES treatment is well received by CHF and COPD patients and brings about increased exercise tolerance, as well as better quality of life. Devices used for NMES therapy, due to progressive miniaturization, are easily accessible and relatively inexpensive.